2018
DOI: 10.1111/jnc.14576
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal biogenesis as an emerging target of neurodevelopmental pathologies

Abstract: Development of the nervous system is carried out by complex gene expression programs that are regulated at both transcriptional and translational level. In addition, quality control mechanisms such as the TP53-mediated apoptosis or neuronal activity-stimulated survival ensure successful neurogenesis and formation of functional circuitries. In the nucleolus, production of ribosomes is essential for protein synthesis. In addition, it participates in chromatin organization and regulates the TP53 pathway via the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 187 publications
(289 reference statements)
5
79
0
Order By: Relevance
“…Increasing evidence points to a critical link between dysregulated ribosome biogenesis and neurodevelopmental pathologies, including microcephaly 48 . The clinical features observed in patients mutated in RRP7A, however, differ from the usual findings in patients with mutations in genes associated with ribosome biogenesis.…”
Section: R P 7 a + /+ R R P 7 A -/R R P 7 A + /+ R R P 7 A -/R R P 7 mentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence points to a critical link between dysregulated ribosome biogenesis and neurodevelopmental pathologies, including microcephaly 48 . The clinical features observed in patients mutated in RRP7A, however, differ from the usual findings in patients with mutations in genes associated with ribosome biogenesis.…”
Section: R P 7 a + /+ R R P 7 A -/R R P 7 A + /+ R R P 7 A -/R R P 7 mentioning
confidence: 99%
“…Analyses of human foetal brain sections, zebrafish, cell models, and primary cells from patients show that RRP7A levels and functionality is critical in neocortex development and neurogenesis and provide evidence for defective ribosome biogenesis as well as resorption of the primary cilium as pathophysiological mechanisms. Interestingly, recent studies have shown that microcephaly caused by neural tissue infection of flaviviruses, including Zika virus (ZIKV) as well as Japanese encephalitis, West Nile, and Dengue viruses, in part is associated with localization of virus-encoded proteins to both nucleoli 48,60 and the base of primary cilia 61 in conjunction with dysregulated ribosome biogenesis 48 , aberrant length control of primary cilia, and uncontrolled cell fate determination of NPCs 61,62 . In support of both nucleolar and ciliary functions, co-IP analyses and global interactomics confirmed ZIKV-host interactions to key regulatory components of both the cilium-centrosome axis and nucleoli, including NOL6 61,63 .…”
Section: R P 7 a + /+ R R P 7 A -/R R P 7 A + /+ R R P 7 A -/R R P 7 mentioning
confidence: 99%
“…Though ribosomopathies have consequences throughout the body, some ribosomal subunit mutations are connected specifically to neurological disorders, such as those linked to cases of Autism Spectrum Disorder (ASD) and intellectual disability (ID) (Hetman and Slomnicki, 2019;Choe and Cho, 2020). Defects in ribosome function have also been connected to neurodegenerative diseases such as Alzheimer's disease (AD) (Ding et al, 2005;Hernández-Ortega et al, 2016) and Parkinson's disease (PD) (Taymans et al, 2015), and ribosomal frameshifting is implicated in repeat expansion disorders such as Huntington's disease (HD) and Amyotrophic Lateral Sclerosis (ALS) (Gao et al, 2017).…”
Section: Protein Synthesis Linked To Neurological Diseasementioning
confidence: 99%
“…Genes responsible for ensuring the translational capacity of the cell play a prominent role in brain development and function [1][2][3] . This emerging link highlights the necessity to understand the diverse and dynamic molecular cues orchestrating assembly of the translation machinery 4 .…”
Section: Introductionmentioning
confidence: 99%